The pregnane X receptor (PXR) and the nuclear receptor corepressor 2 (NCoR2) modulate cell growth in head and neck squamous cell carcinoma - Rigalli, Juan Pablo; Reichel, Matthias; Reuter, Tasmin; Tocchetti, Guillermo Nicolás; Dyckhoff, Gerhard; Herold-Mende, Christel; Theile, Dirk; Weiß, Johanna (PLOS ONE, 2018)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most frequent cancer worldwide. The pregnane X receptor (PXR) is a nuclear receptor regulating several target genes associated with cancer malignancy. We here demonstrated a significant effect of PXR on HNSCC cell growth, as evidenced in PXR knock-down experiments. PXR transcriptional activity is more importantly regulated by the presence of coactivators and corepressors than by PXR protein expression. To date, there is scarce information on the regulation of PXR in HNSCC and on its role in the pathogenesis of this disease. Coactivator and corepressor expression was screened through qRT-PCR in 8 HNSCC cell lines and correlated to PXR activity, determined by using a reporter gene assay. All cell lines considerably expressed all the cofactors assessed. PXR activity negatively correlated with nuclear receptor corepressor 2 (NCoR2) expression, indicating a major role of this corepressor in PXR modulation and suggesting its potential as a surrogate for PXR activity in HNSCC. To test the association of NCoR2 with the malignant phenotype, a subset of three cell lines was transfected with an over-expression plasmid for this corepressor. Subsequently, cell growth and chemoresistance assays were performed. To elucidate the mechanisms underlying NCoR2 effects on cell growth, caspase 3/7 activity and protein levels of cleaved caspase 3 and PARP were evaluated. In HNO97 cells, NCoR2 over-expression decreased cell growth, chemoresistance and increased cleaved caspase 3 levels, caspase activity and cleaved PARP levels. On the contrary, in HNO124 and HNO210 cells, NCoR2 over-expression increased cell growth, drug resistance and decreased cleaved caspase 3 levels, caspase activity and cleaved PARP levels. In conclusion, we demonstrated a role of PXR and NCoR2 in the modulation of cell growth in HNSCC. This may contribute to a better understanding of the highly variable HNSCC therapeutic response.